Organic metal engineering for enhanced field-effect transistor performance. Issue 40 (10th September 2014) - Pfattner, Raphael; Rovira, Concepció; Mas-Torrent, Marta
Abstract : The use of charge transfer salts in OFETs offers unique possibilities for enhancing the device performance. Abstract : A key device component in organic field-effect transistors (OFETs) is the organic semiconductor/metal interface since it has to ensure efficient charge injection. Traditionally, inorganic metals have been employed in these devices using conventional lithographic fabrication techniques. Metals with low or high work-functions have been selected depending on the type of semiconductor measured and, in some cases, the metal has been covered with molecular self-assembled monolayers to tune the work function, improve the molecular order at the interface and reduce the contact resistance. However, in the last few years, some approaches have been focused on utilizing organic metals in these devices, which have been fabricated by means of both evaporation and solution-processed techniques. Higher device performances have often been observed, which have been attributed to a range of factors, such as a more favourable organic/organic interface, a better matching of energy levels or/and to a reduction of the contact resistance. Further, in contrast to their inorganic counterparts, organic metals allow their chemical modification and thus the tuning of the Fermi level. In this perspective paper, an overview of the recent work devoted to the fabrication of OFETs with organic metals as electrodes will be carried out. It will be shown that in these devices not only is the matching of the HOMO or LUMO of the semiconductor with the metal work-function important, but other aspects such as the interface morphology can also play a critical role. Also, recent approaches in which the use of organic charge transfer salts as buffer layers at the metal contacts or on the dielectric or as doping agents of the organic semiconductors that have been used to improve the device performance will be briefly described.